2019
DOI: 10.21276/ijcmsr.2019.4.1.23
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomographic Evaluation of Mediastinal Mass Lesions

Abstract: The multitude of diseases affecting the mediastinum varies considerably, comprising of tumors (benign to extremely malignant), cysts, vascular anomalies, lymph node masses, mediastinitis, mediastinal fibrosis, and pneumomediastinum. Current research aimed to study the computed tomographic characteristics of Mediastinal mass lesions in Plain and Contrast-enhanced scans and to study the distribution of mediastinal masses and their extension to adjacent structures and compare the CT findings with pathological dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…In a study by VV Hattiholi et al [14] S Satbeer Singh et al [15] in their study CT evaluation of mediastinal mass lesions in 2019 concluded that cough 44% , dyspnoea 38% , fever 20% , chest pain 20% were among the most common symptoms along with few asymptomatic cases, lesions of anterior mediastinum 52%, middle mediastinum 18%, and posterior mediastinum 30%. thymic masses 26.9% was most common anterior lesion followed by metastatic lymph node 19.2%, tuberculous lymph node 15.4%, aortic mass 15.4%, lymphoma were 11.6%, thyroid mass about 7.7% and germ cell tumour were seen in remaining 3.8%.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by VV Hattiholi et al [14] S Satbeer Singh et al [15] in their study CT evaluation of mediastinal mass lesions in 2019 concluded that cough 44% , dyspnoea 38% , fever 20% , chest pain 20% were among the most common symptoms along with few asymptomatic cases, lesions of anterior mediastinum 52%, middle mediastinum 18%, and posterior mediastinum 30%. thymic masses 26.9% was most common anterior lesion followed by metastatic lymph node 19.2%, tuberculous lymph node 15.4%, aortic mass 15.4%, lymphoma were 11.6%, thyroid mass about 7.7% and germ cell tumour were seen in remaining 3.8%.…”
Section: Discussionmentioning
confidence: 99%